(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article explores the relationship between the knowledge of English idioms and language proficiency, as well as its impact on the effectiveness of intercultural communication. It examines the role of idioms in linguistic competence, the challenges non-native speakers face when interpreting them, and the strategies employed to overcome these difficulties. The findings highlight the importance of idiom instruction for achieving advanced English proficiency and ensuring successful intercultural communication.